2015
DOI: 10.1017/s0030605315000381
|View full text |Cite
|
Sign up to set email alerts
|

Nature and extent of human–elephant Elephas maximus conflict in central Nepal

Abstract: Human–elephant conflict is one of the main threats to the long-term survival of the Asian elephant Elephas maximus. We studied the nature and extent of human–elephant interactions in the buffer zones of Chitwan National Park and Parsa Wildlife Reserve in Nepal, through household questionnaire surveys, key informant interviews, site observations, and analysis of the reported cases of damage during January 2008–December 2012. During this 5-year period 290 incidents of damage by elephants were reported, with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 15 publications
14
64
0
Order By: Relevance
“…Our study found that the risk of elephant damage was more on the settlements located nearby the Jalthal forest compared to areas further than the forest. Similar findings were recorded in study by Pant et al (2016) which showed that the incidents of elephant damages decreased proportionately with increase in distance from the park boundary in buffer zones of Chitwan National Park and Parsa National P ark. In terms of HEC incidents, crop damage including paddy was more frequently recorded in Jalthal area.…”
Section: Discussionsupporting
confidence: 86%
“…Our study found that the risk of elephant damage was more on the settlements located nearby the Jalthal forest compared to areas further than the forest. Similar findings were recorded in study by Pant et al (2016) which showed that the incidents of elephant damages decreased proportionately with increase in distance from the park boundary in buffer zones of Chitwan National Park and Parsa National P ark. In terms of HEC incidents, crop damage including paddy was more frequently recorded in Jalthal area.…”
Section: Discussionsupporting
confidence: 86%
“…ten Velde (1997) revealed that the same bull elephants were raiding crops in both Parsa and Chitwan areas and also in the adjoining reserve forests. This trend has continued, with one of the bull elephants in central Nepal being responsible for most of the human-elephant conflict incidents from 2010 onwards (Pant et al 2015).…”
Section: Elephant Populations and Crop Raidingmentioning
confidence: 98%
“…In Chitwan National Park (CNP) most poor people living near forests are of indigenous ethnicity and a lower caste, have no or few work opportunities, receive informal education and typically own a smaller piece of land, and survival problems are more acute for them than conservation issues. In places where people and wildlife share the same landscape for resource usage, wildlife leaves negative impacts on people and vice versa [1][2][3][4][5][6][7][8][9][10]. In addition, wildlife damage leads to resentment and people resort to retaliatory killings, even of endangered species.…”
Section: Introductionmentioning
confidence: 99%
“…Heinen and Mehta [13] stated that the buffer zone in Nepal has granted local participation but the managerial structure remains largely top down with regard to the Park's Warden regulatory role. Other studies (e.g., tiger: [7,14] and elephant: [8,15]) addressed issues of wildlife attacks on people and recorded injury and death cases in the landscapes of CNP and its neighborhoods. However, there is no simple formula for combining conservation objectives with local needs [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation